Campus-Based Sharia Activism: Exploring Legal Awareness and Youth Mobilization in Muslim Communities - Agus Setiawan; Ahmad Purkoni; Fajli Aijat Mau; Agung Setiawan; Ahmad Mufti (Mabadi Iqtishad Al Islami, 2025)
This study explores the rise of campus-based Sharia activism and its influence on legal consciousness and youth mobilization within Muslim communities, particularly in Southeast Asia. Amid increasing religiosity among Muslim students, campus organizations such as Lembaga Dakwah Kampus (LDK) have played pivotal roles in shaping Islamic legal understanding through peer-based intellectualism, digital engagement, and gender-inclusive discourse. Despite growing activism, empirical research remains limited, prompting this study to adopt a library research methodology. Drawing from academic sources published over the past five years, the study employs qualitative content analysis to identify key patterns and themes related to youth engagement with Sharia law. The findings reveal that student activism fosters a dynamic legal consciousness that blends traditional jurisprudence with contemporary concerns such as human rights, gender equity, and digital ethics. Peer-led discussions, digital platforms, and inclusive legal education emerge as crucial tools in this transformation. Youth activists are not passive recipients of religious authority but active agents who reinterpret Sharia in light of lived realities.